(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper is concerned with the concepts of weakly (τ_1,τ_2)β-open functions and weakly (τ_1,τ_2)β-closed functions. Furthermore, several characterizations of weakly (τ_1,τ_2)β-open functions and weakly (τ_1,τ_2)-closed functions are investigated.